Antifungal Efficacy of Chitosan against Blast Pathogenic Fungi (Magnaporthe oryzae) on Rice (Oryzasativa) Field - Aremu, M. B.; Adebola, M. O.; Salaudeen, M. T.; Egwim, C. E.; Gbadeyan, S. T.; Daudu, O. A. Y. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Blast disease (caused by Magnaporthe oryzae) is the most damaging disease to rice, and synthetic fungicides has been the primary means of control, however, concerns have been raised about the health risks posed, hence, the need for alternative biological crop protection strategies. This study evaluate the antifungal efficacy of chitosan against blast pathogenic fungi on rice field. Three chitosan (High, Medium and Low Molecular Weight) were purchased while the fourth Chitosan was synthesized from crab shell (CSCS). Faro 52 rice variety was collected from National Cereal Research Institute, Badeggi and Planted on Hydromorphic field. The degree of deacetylation of the synthesized chitosan was 98%. The rice field was inoculated with M. oryzae and treated with chitosan at two weeks after transplanting. The blast severity and incidence and other agronomic data were taken and data were analyzed using Analysis of Variance (ANAOVA) and means separated using Duncan multiple range test (DMRT). Results reveals that blast severity of 6,(highly susceptible) 5, (moderately susceptible) 4(susceptible) and incidence of 28.3%, 20%, 20% and 24.3% in rice plant tag with MMWC1.5%, 1HMWC 2.0%, LMWC2.0% and CSCS 2.0% before treatment with chitosan was observed. However, the severity reduce to 1(resistance) in all and incidence of 9.3%, 2.3%, 1.0% and 2.0% respectively at the end of the treatment. There was no significant difference (P≤0.05) in all other agronomic parameters except for panicle count with highest value (8.53) in HMWC 2.0% and lowest value (5.80) in HMWC 0.5%. Similarly, significant difference was observed in grain yield per plot with highest yield of 717 gram in HMWC 2.0% treated plot while the lowest yield of 190 gram was observed in MMWC 0.5% which was significantly different. It may therefore be concluded that chitosan treatment reduce the severity and incidence of blast pathogen as well as increase grain yield.